2017
DOI: 10.1007/s11547-017-0833-8
|View full text |Cite
|
Sign up to set email alerts
|

Haralick’s texture features for the prediction of response to therapy in colorectal cancer: a preliminary study

Abstract: Five Haralick's features showed significant relevance in the prediction of response to therapy in colorectal cancer and might be used as additional imaging biomarker in the oncologic management of colorectal patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Different types of individual radiomic features were associated with complete pathologic response to CRT [ 37 , 39 – 45 , 47 , 63 ]. The predictive value of entropy, kurtosis, skewness, and tumor volume were most frequently described [ 37 , 40 44 ]. Two studies reported no significant association between PET texture features and pathologic response to CRT in patients with LARC [ 38 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different types of individual radiomic features were associated with complete pathologic response to CRT [ 37 , 39 – 45 , 47 , 63 ]. The predictive value of entropy, kurtosis, skewness, and tumor volume were most frequently described [ 37 , 40 44 ]. Two studies reported no significant association between PET texture features and pathologic response to CRT in patients with LARC [ 38 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Radiomics analysis may provide information, which could impact overall patient prognosis and potential eligibility for target therapies [ 72 ]. A combined model, including the radiomics and clinical features obtained from pretreatment T2-weighted MR images, was able to predict the likelihood of developing distant metastases, thus potentially aiding in tailoring treatment strategies in high-risk patients [ 73 ].…”
Section: Radiomics For the Personalized Management Of Rc Patients: Current Evidence And Perspectivesmentioning
confidence: 99%
“…It suggested that the Kurtosis value of T2WI before treatment could be used as a predictor of the therapeutic effect of nCRT in rectal cancer patients and help physicians guide the follow-up clinical decision-making as well. Another study [19] showed that the Contrast and Entropy of T2WI before treatment could also predict the therapeutic effect of nCRT for CRC.…”
Section: Prediction Of Therapeutic Effect Of Primary Lesionsmentioning
confidence: 99%
“…In addition to the wide applications in MRI, texture analysis technology has been likewise used in CT [19,21] and Pet-ct [22] images to predict the therapeutic effect of nCRT for CRC. Caruso et al [19] found that five texture parameters, including the Energy, Contrast and Correlation and so on, could be used as imaging markers to predict the sensitivity of nCRT in CRC patients.…”
Section: Prediction Of Therapeutic Effect Of Primary Lesionsmentioning
confidence: 99%